2010
DOI: 10.4152/pea.201003173
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Corrosion of Annealed and Aged 18 Ni 250 Grade Maraging Steel in Sulphuric Acid Medium

Abstract: The corrosion behavior of aged and annealed sample of 18 Ni 250 grade maraging steel was investigated in varied conditions of concentration and temperature of sulphuric acid medium, using electrochemical techniques like Tafel polarization and electrochemical impedance spectroscopy (EIS). The results obtained from both the techniques are in good agreement. These results have shown increase in corrosion rate of aged specimen with increase in concentration and temperature of sulphuric acid. With increase in conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…[16] Maraging steels were found to be less susceptible to hydrogen embrittlement than common high-strength steels owing to significantly low diffusion of hydrogen in them. [17] Poornima et al [4] have studied the corrosion behavior of 18 Ni 250 grade maraging steel in a phosphoric acid medium and reported that the corrosion rate of the annealed sample is less than that of the aged sample. Similar observations also have been reported for the corrosion of 18 Ni 250 grade maraging steel in suphuric acid medium.…”
Section: Accepted 19 April 2016mentioning
confidence: 98%
See 2 more Smart Citations
“…[16] Maraging steels were found to be less susceptible to hydrogen embrittlement than common high-strength steels owing to significantly low diffusion of hydrogen in them. [17] Poornima et al [4] have studied the corrosion behavior of 18 Ni 250 grade maraging steel in a phosphoric acid medium and reported that the corrosion rate of the annealed sample is less than that of the aged sample. Similar observations also have been reported for the corrosion of 18 Ni 250 grade maraging steel in suphuric acid medium.…”
Section: Accepted 19 April 2016mentioning
confidence: 98%
“…Similar observations also have been reported for the corrosion of 18 Ni 250 grade maraging steel in suphuric acid medium. [18] In this work, the corrosion behaviour of two grades of cobalt-free as well as conventional maraging steel welded pipe steel in 1 M H 2 SO 4 solutions was investigated using linear polarisation and electrochemical impedance spectroscopy(EIS) techniques.…”
Section: Accepted 19 April 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Finely polished Al 2024 alloy specimens with 1.0 cm 2 surface area were exposed to corrosion medium of different concentrations of hydrochloric acid (1 N, 0.75 N, 0.5 N and 0.25 N) separately at a laboratory temperature [19,20] . The potentiodynamic current-potential curves were recorded by polarizing the specimen to -250 mV cathodically and +250 mV anodically with respect to open circuit potential (OCP) at a scan rate of 0.01 V/s (Figures 1-5).…”
Section: Tafel Polarization Studiesmentioning
confidence: 99%
“…and on the nature of the inhibitor [10]. Sulfuric acid is one of the most aggressive acids for iron and its alloys and is often used during cleaning, pickling, descaling, acidizing, and so forth [11,12]. The inhibitor molecules get bonded to the metal surface by chemisorption, physisorption, or complexation with the polar groups acting as the reactive centers in the molecules [13].…”
Section: Introductionmentioning
confidence: 99%